Menyelisik Sejarah Sastra Pariwisata di Barat dan Indonesia - Pulungan, Alpi Anwar; Wulandari, Sovia; Firismanda, M. A. Haris (Prosiding Seminar Nasional Humaniora, 2025)
This study examines the history and development of literary tourism in the Western and Indonesia. In the West, literary tourism originated from traditions such as visiting authors’ residences, publishing literary biographies, and creating literary maps, which later evolved into modern forms such as fictional character museums and film adaptation sites. In Indonesia, literary tourism is rooted in oral traditions that have developed into literary festivals, writers’ houses, and literary museums. The main difference between the two lies in their orientation and cultural foundations: Western literary tourism is centered on written literacy traditions and the individuality of authors, whereas Indonesian literary tourism emphasizes collective cultural values. This research employs a qualitative approach using library research methods to explore and analyze written sources related to literary tourism. The findings indicate that literary tourism in both regions continues to develop as an integral part of modern cultural tourism. Abstrak Penelitian ini membahas sejarah dan perkembangan wisata sastra di Barat dan Indonesia. Di Barat, wisata sastra berawal dari tradisi kunjungan ke rumah sastrawan, penerbitan biografi, dan peta sastra, yang kemudian berkembang menjadi bentuk modern seperti museum karakter fiksi dan lokasi film adaptasi karya sastra. Sementara itu, di Indonesia, wisata sastra berakar pada tradisi lisan yang berkembang menjadi festival sastra, rumah sastrawan, dan museum sastra. Perbedaan utama keduanya terletak pada orientasi dan basis kultural: Barat berpusat pada tradisi literasi tertulis dan individualitas pengarang, sedangkan Indonesia menonjolkan nilai budaya kolektif. Penelitian ini menggunakan metode kualitatif dengan studi kepustakaan untuk menelusuri dan menganalisis sumber tertulis terkait sastra pariwisata. Hasil penelitian menunjukkan bahwa wisata sastra di kedua wilayah terus berkembang sebagai bagian dari pariwisata budaya modern.